Factors Affecting Clinical Outcomes Among Patients Infected With HIV and Anal Cancer Treated With Modern Definitive Chemotherapy and Radiation Therapy - Neil T. Pfister, MD, PhD; Yichun Cao, MPH; Ashely J. Schlafstein, MD; Jeffrey Switchenko, PhD; Pretesh R. Patel, MD; Mark W. McDonald, MD; Sibo Tian, MD; Jerome C. Landry, MD; Olatunji B. Alese, MD; Clifford Gunthel, MD; Jolinta Y. Lin, MD (Advances in Radiation Oncology, 2023)
Purpose: Anal cancer affects a disproportionate percentage of persons infected with human immunodeficiency virus (HIV). We analyzed a cohort of patients with HIV and anal cancer who received modern radiation therapy (RT) and concurrent chemotherapy to assess whether certain factors are associated with poor oncologic outcomes. Patients and Methods: We performed a retrospective chart review of 75 consecutive patients with HIV infection and anal cancer who received definitive chemotherapy and RT from 2008 to 2018 at a single academic institution. Local recurrence, overall survival, changes in CD4 counts, and toxicities were investigated. Results: Most patients were male (92%) with large representation from Black patients (77%). The median pretreatment CD4 count was 280 cells/mm3, which was persistently lower at 6 and 12 months’ posttreatment, 87 cells/mm3 and 182 cells/mm3, respectively (P < .001). Most (92%) patients received intensity modulated RT; median dose was 54 Gy (Range, 46.8-59.4 Gy). At a median follow-up 5.4 years (Range, 4.37-6.21 years), 20 (27%) patients had disease recurrence and 10 (13%) had isolated local failures. Nine patients died due to progressive disease. In multivariable analysis, clinically node negative involvement was significantly associated with better overall survival (hazard ratio, 0.39; 95% confidence interval, 0.16-1.00, P = .049). Acute grade 2 and 3 skin toxicities were common, at 83% and 19%, respectively. Acute grade 2 and 3 gastrointestinal toxicities were 9% and 3%, respectively. Acute grade 3 hematologic toxicity was 20%, and one grade 5 toxicity was reported. Several late grade 3 toxicities persisted: gastrointestinal (24%), skin (17%), and hematologic (6%). Two late grade 5 toxicities were noted. Conclusions: Most patients with HIV and anal cancer did not experience local recurrence; however, acute and late toxicities were common. CD4 counts at 6 and 12 months’ posttreatment remained lower than pretreatment CD4 counts. Further attention to treatment of the HIV-infected population is needed.